Enhanced photocatalytic and antibacterial activities of S-scheme SnO2/Red phosphorus photocatalyst under visible light. (June 2022) - Aihemaiti, Xiadiye; Wang, Xin; Li, Yunpeng; Wang, Yun; Xiao, Lu; Ma, Yuhua; Qi, Kezhen; Zhang, Yu; Liu, Jing; Li, Jinyu
Abstract: The construction of wide bandgap semiconductors with heterojunctions is an effective strategy to improve the photocatalytic activity of narrow-bandgap semiconductors, such as red phosphorus (RP). The novel step-scheme (S-scheme) heterojunction can separate photocarriers effectively while retaining the high reduction-oxidation capacity of the catalyst. Herein, a SnO2 /hydrothermally treated RP (SnO2 /HRP) S-scheme heterojunction was constructed and was found to display superior performance in the photocatalytic degradation of pollutants and the disinfection of bacteria. The 5%SnO2 /HRP (mass ration of SnO2 with 5 wt%) composite had the strongest photocatalytic activity. It could degrade 97.5% of Rhodamine B (RhB) after 12 min of light exposure. The photodegradation rate constant of this composite reached 2.96 × 10 −1 min −1, which was 4.4 and 59.2 times higher than that of pure HRP and SnO2, respectively. Furthermore, this S-scheme heterojunction composite exhibited a higher efficient photocatalytic antibacterial rate (99.4%) for Escherichia coli ( E. coli ) under visible-light irradiation, than pure HRP (66.4%) and SnO2 (72.9%). Further mechanistic investigations illustrated that the intimate contact between HRP and SnO2 in the S-scheme system heterojunction could effectively boost carrier transfer and improve the photocatalytic activity of the semiconductor. This investigation provided an efficient recyclable S-scheme heterojunction composite for the photocatalytic degradation of pollutants and bacteria. Graphical abstract: Image 1 Highlights: SnO2 /HRP S-scheme heterojunction accelerated transfer of photogenerated carriers. Antibacterial rate of composite against E. coli was 99.4% after 30 min. Photodegradation rate of composite was higher than that of HRP and SnO2 . Much more hydroxyl radicals were generated in 5%SnO2 /HRP composite.